Rethinking Blue Carbon: Between Climate Finance and Social Equity in Coastal Communities - Mentari, Nikmah; Ilham Dwi Rafiqi; Putu Narayana Mahagotra (Faculty of Law, University of Mataram, 2025)
Blue carbon ecosystems—such as mangroves, seagrasses, and tidal marshes—are increasingly recognized as vital natural carbon sinks in global climate change mitigation efforts. This recognition has triggered a surge in climate finance initiatives targeting coastal areas, promising both ecological restoration and economic benefits. However, the implementation of blue carbon investment schemes often reveals a paradox: while these projects are framed as climate solutions, they frequently marginalize coastal communities, restrict access to traditional resources, and concentrate benefits among powerful stakeholders. This article critically examines the intersection of blue carbon finance and social equity, with a specific focus on legal and policy frameworks in Indonesia, complemented by comparative insights from global practices. Using a normative legal research, the study analyzes the gaps in existing regulatory instruments, the limitations of community participation, and the risks of “carbon colonialism” embedded in current investment models. This article uses a conceptual approach and a statutory approach. This research focuses on blue carbon management as one of the investment products in the carbon exchange with the type of SPE-GRK. It argues that for blue carbon to serve as a tool for climate justice, reforms must ensure fair benefit-sharing, community-driven governance, and legal safeguards that protect the rights of coastal populations. The article concludes by proposing a rights-based and inclusive framework for blue carbon policies that aligns environmental goals with social equity imperatives.